Flow Characteristics in Perforated Subsurface Drain of Drainage System Application: Case Study of Gate Fully Open with Longitudinal Slope 1/500 - Abdullah, Junaidah; Mohd Arif Zainol, Mohd Remy Rozainy; Yusof, Mohd Fazly; Mohd Kasim, Muhammad Zaki; Alias, Muhamad Nurfasya; Ayub, Khairul Rahmah; Juiani, Siti Fairuz; Azizan, Nor Ariza; Shaharuddin, Syafiq; Zainalfikry, Muhammad Kashfy; Zakaria, Nor Azazi; Ab Ghani, Aminuddin (International Journal of Integrated Engineering, 2023)
Subsurface drainage is part of a sustainable drainage system’s components. This component represents the infiltration of stormwater into the subsurface drainage system for flow attenuation purposes. This study examines the flow parameters of subsurface drainage components. The laboratory validation of perforated subsurface drains was conducted at a longitudinal slope gradient of 1/500 with the Gate Fully Open. The manning, n data obtained in these experiments varies with several hydraulic parameters. Therefore, the experimental relationship between the flow characteristics of these subsurface drain components has been investigated. The relationship between flow behavior has been determined. The sub-critical and supercritical, and turbulence flow has occurred in this study